Sejarah Amalan Sihir di Zaman Para Nabi Menurut Sumber Tafsir dan Hadith - Hj. Ali @ Mat Zin, Aizan; Hj Mohd Yusoff, Mohd Yakub @ Zulkifli (Jurnal Usuluddin, 2003)
This concise article deals with the history of black magic according to the Islamic sources, especially al-Qur'an and the Prophet's Traditions (Hadith). The Qur'anic interpretations were based on mufassirun exegesis. By scrutinising the exegesis, it was clear that this practise was rooted from the two sinned angels who were sent to this world. Furthermore the stories extracted from the Qur'anic source will differentiate between black magic and mukjizat which was given by Allah S.W.T to the selected Prophets.